Risk Assessment in Hereditary Colorectal Cancer Family by Using APC and MSH2 mRNA Gene Expression and Bayesian Analysis - Tjahjadi Robert Tedjasaputra; Mochammad Hatta; Muhammad Nasrum Massi; Rosdiana Natzir; Ilhamjaya Patellongi; Marcellus Simadibrata; Ibrahim Labeda; Rina Masadah; Muhammad Luthfi Parewangi; Prihantono Prihantono; Andi Asadul Islam; Agussalim Bukhari; Budu Budu; Rinda Nariswati (The Prodia Education and Research Institute (PERI), 2020)
BACKGROUND: Some of colorectal cancers (CRCs) are familial, however, heterozygote relatives have approximately 80% lifetime risk of cancer. Risk assessment of CRC’s family could be calculated by direct measurement of mRNA gene expression and Bayesian theorem which is modifying initial background of pedigree risk with additional conditional information. This application has not been reported.METHODS: The cross-sectional translational sequential studies were performed: (1) adenomatous polyposis coli (APC) and MutS homolog (MSH)2 mRNA quantitative RT PCR gene expressions in tissue and whole blood CRC patients; (2) gene expression was determined in matched controls; and (3) pedigree and Bayesian analysis was calculated in the patient’s family of Proband.RESULTS: Fourty CRC and 31 control subjects were enrolled. The mean blood APC level control’s group was 13,261±670 fold-change (fc) and blood MSH2 level was 12,219±756 fc. The cut-off points for hereditary APC was 12,195 fc and MSH2 was 11,059 fc. The mean APC blood level in CRC subject was 11,578±2,638 fc and MSH2 blood level was 11,411±2,912 fc. There were significant differences APC and MSH level between tissue and blood level in CRC. Eight of 40 CRC subjects had a history of familial CRC. Four patients and 10 Probands were available for recurrence risk evaluation of pedigree analysis, RNA PCR quantitative and Bayesian calculation.CONCLUSION: There was determined a cut-off point of hereditary mRNA quantitative expression. The APC and MSH2 levels in CRC subjects were significantly lower than controls. Bayesian analysis allowed for the calculation of relative risk in CRC family members and considered in clinical practice.KEYWORDS: hereditary CRC, APC gene, MSH gene, Bayesian analysis